Effect of blood on the assay of 6-phosphogluconate dehydrogenase in vaginal fluid - Gibbs, D. F. (1968)
The effect of blood in vaginal fluid on the assay of 6-phosphogluconate dehydrogenase has been studied. Alternative assay procedures have been investigated to overcome these effects.